2017
DOI: 10.1177/0734242x17691344
|View full text |Cite
|
Sign up to set email alerts
|

Hospital waste management in developing countries: A mini review

Abstract: Health care activities can generate different kinds of hazardous wastes. Mismanagement of these wastes can result in environmental and occupational health risks. Developing countries are resource-constrained when it comes to safe management of hospital wastes. This study summarizes the main issues faced in hospital waste management in developing countries. A review of the existing literature suggests that regulations and legislations focusing on hospital waste management are recent accomplishments in many of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
160
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(192 citation statements)
references
References 87 publications
2
160
0
12
Order By: Relevance
“…There is marked discrepancy in waste generation rates within each country and across countries. In general, hospitals in developing countries suffer from poor practices in waste sorting and segregation, handling, storage, transport, and final disposal (Ali et al 2017). In Egypt, the issue of hazardous medical wastes management has acquired an increasing interest in the last two decades, as the awareness of their serious health effects has increased on both public and governmental levels (Shouman et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…There is marked discrepancy in waste generation rates within each country and across countries. In general, hospitals in developing countries suffer from poor practices in waste sorting and segregation, handling, storage, transport, and final disposal (Ali et al 2017). In Egypt, the issue of hazardous medical wastes management has acquired an increasing interest in the last two decades, as the awareness of their serious health effects has increased on both public and governmental levels (Shouman et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear why the use of nomenclature vary in countries, and yet, there is only one global manual. More so, the adverse consequences of the improper management of HCW have been documented extensively [2,[18][19][20][21][22][23], and using different nomenclatures to describe HCW is one of the factors contributing to the improper segregation practices of HCW among healthcare workers [4]. For example, a study in Botswana on HCWM current practices in healthcare facilities [16] found that the term 'clinical waste' is known to mean all of the waste that is generated from healthcare facilities.…”
Section: Discussionmentioning
confidence: 99%
“…However, the healthcare waste (HCW) that is generated during these healthcare activities could have adverse effects on both the people and the environment if it is poorly managed [2,3]. The literature regarding healthcare waste management (HCWM) shows that large volumes of HCW is generated from healthcare facilities globally [4], and it is poorly managed, especially in low and middle-income countries (LMICs) [5]. The main factors attributed to poor HCWM practices in LMICs include: lack of financial investment and clear policies to manage HCW by most governments [3][4][5][6], low levels of knowledge by healthcare staff on how to handle HCW properly [7,8], poor segregation practices among healthcare workers [9], and inappropriate transport for transporting HCW, which is driven by untrained drivers who are also not registered to handle HCW [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dialysis is at the heart of the matter as it is one of the most important waste producers in medicine [7][8][9][10]. Waste management involves not only ecological factors, it also has an important economic impact, since the disposal of potentially hazardous or contaminated waste, which by definition is all hospital waste that has been in contact with any kind of biological fluid, can be extremely expensive, and represents a problem increasingly felt to be crucial in developing countries [10][11][12][13][14][15].…”
Section: Dialysis In the Global Contextmentioning
confidence: 99%